Stagnant wages, sectoral misallocation and slowing productivity growth - Michaela Schmöller (Bank of Finland, 2019)
I propose a two-sector endogenous growth model with heterogeneous sectoral productivity and sector-specific, nonlinear hiring costs to analyse the link between sectoral resource allocation, low productivity growth and stagnant real wages. My results suggest that an upward shift in the labor supply, triggered for instance by a labor market reform, as among others implemented in Germany in 2003-2005, is beneficial in the long-run as it raises growth of technology, labor productivity and real wages. I show, however, that in the immediate phase following the labor supply shock, labor productivity and real wages stagnate as employment gains are initially disproportionally allocated to low-productivity sectors, limiting the capacity for technology growth and depressing real wages and productivity. I demonstrate that due to the learning-by-doing growth externality in the high-productivity sector the competitive equilibrium is ineffcient as firms fail to internalize the effect of their labor allocation on aggregate growth. Subsidies to high-productivity sector production can alleviate welfare losses along the transition path.
URN:NBN:fi:bof-201905061173
Keywords: E20; E24; E60; O40; O41; 330